2019
DOI: 10.1007/s12008-019-00571-w
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic strategy for optimizing product design considering the production costs

Abstract: This article describes a new interactive design approach integrating the constraints associated with production include manufacturing and assembling. The proposed method, in the form of an algorithm, allows optimisation of product design by minimizing production costs at each iteration, without compromising its functionality. The novelty of this algorithm in terms of modeling and optimisation of production costs in the design phase is its ability to dynamically evaluate the cumulative costs of production as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To this end, the optimization can relate to the variation in cutting speeds but also to the geometric variation of the member so as to minimize its passage over the energy-consuming machine. The digital continuity between design and industrialization and production can generate a very promising global optimization context [19,20].…”
Section: Architecturementioning
confidence: 99%
“…To this end, the optimization can relate to the variation in cutting speeds but also to the geometric variation of the member so as to minimize its passage over the energy-consuming machine. The digital continuity between design and industrialization and production can generate a very promising global optimization context [19,20].…”
Section: Architecturementioning
confidence: 99%
“…In this regard, the total cost of industrialization of a product estimated by the ABC method represents the sum of the costs of the different activities that contribute to its manufacture, and it is expressed as follows [25]: (10) Where C represents the total cost of industrializing the product, N represents the number of activities, and 𝐶 𝑎𝑐𝑡𝑖𝑣𝑖𝑡𝑖𝑒𝑠 𝑖 represents the cost of activity i. The latter is expressed as follows [25]: The prevision of the costs of the activities of different manufacturing processes using the ABC method is available in the literature, namely for machining [25] , casting [26], forging [27], etc.…”
Section: 2manufacturing Cost Formulationmentioning
confidence: 99%
“…Regarding the optimization of the manufacturing cost, [9] and [5] have developed an approach which allows to obtain the best dimensions and geometric tolerances which optimize the total cost of a pump. In [10] was proposed a study that focuses on the optimization of the manufacturing cost by genetic algorithms. The manufacturing cost is estimated using an analytical method and the variables of the problem are the geometric dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…This is because engineers do not work in isolation, but rather as a team. Adjoul et al [30] observed that optimisations in the production phase required experts from both production and design to work together to create an optimal product. The entire life cycle of a product must be considered when dealing with optimisations.…”
Section: A Genetic Algorithmsmentioning
confidence: 99%